Environmental governance on solid waste management in the Philippines - Era, Marlon de Luna (Animo Repository, 2014)
This examination of environmental governance focuses on Social Private Partnerships (SPPs) in solid waste management. The study looks into the trajectory of environmental governance, the roles and the specific tasks particularly in the performance of Non-State Actors roles and the accountability involved. The research took as a case study of solid waste management implementation in the City of Santa Rosa, Province of Laguna under the social private partnerships highlighting non-state actors such as the NGOs, churches, academic institutions, and industries that are engaged in partnerships. The study made use of data from surveys, focus group discussions and interviews to determine the strengths and weaknesses of different partnership arrangements in the implementation of SWM City of Santa Rosa. The thesis puts forward some recommendations for improvements of partnerships in environmental governance, particularly in the area of law, policy, education and research. For instance, there are recommendations re requirements to document activities, submit reports, auditing, monitoring of partner participation , improving incentives for good accountability and clarifying legal requirements. The overall conclusion is that, for successful environmental governance in this field, a combination of partnership arrangements could promote improved incentives and accountability among non-state actors.